Power, Pleasure, and Profit - Wootton, David (Tantor Media, Inc., 2018)
We pursue power, pleasure, and profit. We want as much as we can get, and we deploy instrumental reasoning-cost-benefit analysis-to get it. We judge ourselves and others by how well we succeed. It is a way of life and thought that seems natural, inevitable, and inescapable. As David Wootton shows, it is anything but. In Power, Pleasure, and Profit, he traces an intellectual and cultural revolution that replaced the older systems of Aristotelian ethics and Christian morality with the instrumental reasoning that now gives shape and purpose to our lives. Wootton guides us through four centuries of Western thought to show how new ideas about politics, ethics, and economics stepped into a gap opened up by religious conflict and the Scientific Revolution. As ideas about godliness and Aristotelian virtue faded, theories about the rational pursuit of power, pleasure, and profit moved to the fore. The new instrumental reasoning cut through old codes of status and rank, enabling the emergence of movements for liberty and equality. But it also helped to create a world in which virtue, honor, shame, and guilt count for almost nothing, and what matters is success. Is our world better for the rise of instrumental reasoning? To answer that question, Wootton writes, we must first recognize that we live in its grip.